Connexin43 Contributes to Inflammasome Activation and Lipopolysaccharide-Initiated Acute Renal Injury via Modulation of Intracellular Oxidative Status - Huang, Yanru; Mao, Zhimin; Zhang, Zhen; Obata, Fumiko; Yang, Xiawen; Zhang, Xiling; Huang, Yong; Mitsui, Takahiko; Fan, Jianglin; Takeda, Masayuki; Yao, Jian (Antioxidants & redox signaling, 2019)
Inflammasome activation plays a pivotal role in many inflammatory diseases. Given that connexin (Cx) channels regulate numerous cellular events leading to inflammasome activation, we determined whether and how connexin affected inflammasome activation and inflammatory cell injury. Exposure of mouse peritoneal macrophages (PMs) to lipopolysaccharide (LPS) plus ATP caused NLRP3 inflammasome activation, together with an increased connexin43 (Cx43). Inhibition of Cx43 blunted inflammasome activation. Consistently, PMs from the Cx43 heterozygous mouse (Cx43 ) exhibited weak inflammasome activation, in comparison with those from the Cx43 mouse. Further analysis revealed that inflammasome activation was preceded by an increased reactive oxygen species (ROS) production, nicotinamide adenine dinucleotide phosphate hydrogen (NADPH) oxidase 2 (NOX2), protein carbonylation, and mitogen-activated protein kinase (MAPK) activation. Suppression of ROS with antioxidant, downregulation of NOX2 with small interfering RNA (siRNA), or inhibition of NADPH oxidase or MAPKs with inhibitors blocked Cx43 elevation and inflammasome activation. Intriguingly, suppression of Cx43 also blunted NOX2 expression, protein carbonylation, p38 phosphorylation, and inflammasome activation. In a model of acute renal injury induced by LPS, the Cx43 mouse exhibited a significantly lower level of blood interleukin-1β (IL-1β), blood urea nitrogen, and urinary protein, together with milder renal pathological changes and renal expression of NLRP3 and NOX4, as compared with the Cx43 mouse. Moreover, inhibition of gap junctions suppressed IL-1β- and tumor necrosis factor-α-induced expression of NOX4 in glomerular podocytes and tubular epithelial cells. Our study indicates that Cx43 contributes to inflammasome activation and the progression of renal inflammatory cell injury through modulation of intracellular redox status. Cx43 could be a novel target for the treatment of certain inflammatory diseases.